Antigen-induced arthritis of the temporomandibular joint via repeated injections of bovine serum albumin in domestic pigs. Issue 6 (June 2019) - Naujokat, Hendrik; Sengebusch, André; Möller, Björn; Wieker, Henning; Açil, Yahya; Wiltfang, Jörg
Abstract: Rheumatoid arthritis (RA) is a chronic inflammatory disease and the temporomandibular joint (TMJ) is affected in up to 50%, resulting in pain, limited mouth opening and dental malocclusion. The outcome of conservative and surgical therapies is unsatisfying in many cases. The purpose of this study was to establish a large animal model of antigen-induced arthritis (AIA) of the TMJ that enables the investigation of the pathogenesis of RA and the evaluation of new therapies. In five domestic pigs, systemic immunization was performed via consecutive intramuscular injections of bovine serum albumin (BSA). Then, AIA was induced via the application of BSA into the TMJ. Injection with saline served as the control. After ten weeks, the joints and adjacent tissues were harvested for histological analysis and cytokine quantification. The changes observed in the AIA specimens included severe synovial inflammation, cartilage-specific glycosaminoglycan content loss, and cartilage surface and discus alterations as well as the formation of chondrocyte clusters. Protein analyses of the synovia showed enhanced levels of IL-1β, IL-6, TNFα and VEGF. A porcine model of immunologic arthritis of the TMJ was successfully established. This model may be used in future studies to investigate the underlying pathogenesis of RA and new therapeutic strategies.